Directional switching of the kinesin Cin8 through motor coupling - Roostalu, Johanna; Hentrich, Christian-Michael; Bieling, Peter; Telley, Ivo A.; Schiebel, Elmar; Surrey, Thomas (Science, 2011)
Kinesin motor proteins are thought to move exclusively in either one or the other direction along microtubules. Proteins of the kinesin-5 family are tetrameric microtubule cross-linking motors important for cell division and differentiation in various organisms. Kinesin-5 motors are considered to be plus-end–directed. However, here we found that purified kinesin-5 Cin8 from budding yeast could behave as a bidirectional kinesin. On individual microtubules, single Cin8 motors were minus-end–directed motors, whereas they switched to plus-end–directed motility when working in a team of motors sliding antiparallel microtubules apart. This kinesin can thus change directionality of movement depending on whether it acts alone or in an ensemble.